Computer Surge. (Beijing Review, 2020)
A total of 2.72 million units of computers were produced in March at LCFC (Hefei) Electronics Technology Co., Ltd, the largest PC research and development and manufacturing base of Chinese tech giant Lenovo, with a record monthly revenue of more than 10 billion yuan ($1.41 billion). On March 27, more than 124,500 units of computers rolled off the production line, registering a record high of daily output at the computer maker in Anhui Province in east China, the LCFC said. The demand for electronic devices with a large display screen such as computers and tablets has surged amid the COVID-19 outbreak when more people are homebound to help contain the spread of the virus.